2016
DOI: 10.1016/j.nut.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium status and the metabolic syndrome: A systematic review and meta-analysis

Abstract: The present systematic review and meta-analysis found an inverse association between Mg intake and MetS. However, the inverse association for serum Mg levels was highly heterogeneous and sensitive. The link between Mg status and MetS should be confirmed by prospective cohort studies controlling the association for other nutrients related to MetS risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 67 publications
(115 reference statements)
4
63
0
5
Order By: Relevance
“…(101) Magnesium can also raise serum HDL-C while reducing LDL-C and TA, through increasing lipoprotein lipase activity among others. (101) Magnesium’s potential effect on weight maintenance was also reported, forming an un-absorbable soap with fatty acids and cholesterol, decreasing their absorption, and thus reducing energy intake from the diet.…”
Section: Discussionmentioning
confidence: 99%
“…(101) Magnesium can also raise serum HDL-C while reducing LDL-C and TA, through increasing lipoprotein lipase activity among others. (101) Magnesium’s potential effect on weight maintenance was also reported, forming an un-absorbable soap with fatty acids and cholesterol, decreasing their absorption, and thus reducing energy intake from the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions such as Type 2 Diabetes [10][11][12], Alzheimer's [13,14] and cardiovascular disease [15,16] have been linked with magnesium deficiency, however the mechanisms of Mg 2+ regulation in such disease states are poorly understood [17,18]. Fluorescent chemosensors, in combination with specialised imaging technologies, provide a useful tool to study the role of metal ions in cellular processes as they enable detection in and around cells with spatial and temporal resolution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have demonstrated that low Mg intake is associated with a higher risk of several cardiovascular and metabolic diseases, including coronary artery disease (3) , hypertension (4) , metabolic syndrome (5) , and diabetes. (6) …”
Section: Introductionmentioning
confidence: 99%